Digital Transformation in OSH Management System: A Study on Indonesian Multi-Level Industry - Dian Afif Arifah; Aisy Rahmania; Ratih Andhika A. Rahma; Siti Ma'rifah; Wegig Wahyu Dwi Santoso (Universitas Airlangga, 2026)
Introduction: Digital transformation in Occupational Safety and Health Management System (OSHMS) increase management efficiency in workplaces. However, the inconsistent adoption may leave safety performance gaps within industries. The rapid digitalisation dynamics along with the small-moderate industrial level domination in Indonesia, raised a question on how the technological gap impacts occupational safety outcomes. The current research explored digital transformation in OSH systems across industry levels in Indonesia and its correlation with organizational size and digital maturity. Method: A quantitative descriptive design was used to describe the digital transformation implemented in OSHMS among various industrial level across regions in Indonesia. Digital Transformation (DT) maturity measured in 5-point likert scale, while the company size defined in terms of the employee size. The Kendall’s tau-b was used to assess the correlation between the extent of DT and the organizational size. Result: Most of the companies were at level 3 (n=53), followed by level 2 of digital maturity. Level 4 was achieved by large companies (15) and one medium-sized company. Correlation tests indicated a positive but statistically non-significant relationship between company size and DT level (Kendall’s tau-b = 0.334, p = 0.065). Conclussion: The findings suggest the potential level of digital transformation available for OSH systems in Indonesia is high, and can be further developed to bring about a shift to a mid OSH digital transformation maturity level. Although larger companies do correlate with the more frequent use of advanced digital technologies, company size by itself is inadequate as a reason why this is occurring.